PERANCANGAN SISTEM INFORMASI REKAM MEDIS DI RS KELUARGA HUSADA BATAM BERBASIS WEB - Oiyana Caesera (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2019)
Information technology is growing rapidly in the development of even all walks of life. Every development makes it easy for the public to receive information quickly. An example in the health sector is in the medical record information system. A medical record is a unit of data from facts or evidence about a patient's history, patient's condition and previous treatments, and written by medical staff who provide health services to patients. Recording medical records by recording in the patient's book is an old method used, and a problem often encountered when using the old medical record system is found to be difficult in managing patient files. This medical record will later be used by medical personnel to add or view patient health records that have been treated. In this study a medical record system was designed using the waterfall method. Waterfall is a systematic and sequential model for information system development. Therefore the researchers developed the system using the waterfall method. The purpose of this medical record information system is to design a medical record information system that can manage patient history data and monthly reports. The system designed is very important because to prevent errors in processing patient data. This application is made based on web using the programming language HTML, PHP, and MYSQL database. So as to produce a web medical record that can be used to make the most disease reports every month, and the number of monthly patient visits using the web-based waterfall method.